Are integrated HIV services less stigmatizing than stand‐alone models of care? A comparative case study from Swaziland. Issue 1 (11th January 2013) - Church, Kathryn; Wringe, Alison; Fakudze, Phelele; Kikuvi, Joshua; Simelane, Dudu; Mayhew, Susannah H; ,
Abstract : Introduction: Integrating HIV with primary health services has the potential to reduce HIV‐related stigma through delivering care in settings disassociated with HIV. This study investigated the relationship between integrated care and felt stigma. The study design was a comparative case study of four models of HIV care in Swaziland, ranging from fully integrated to fully stand‐alone HIV care. Methods: An exit survey ( N =602) measured differences in felt stigma across model of care; the primary outcome "perception of HIV status exposure through clinic attendance" was analyzed using multivariable logistic regression. In‐depth interviews ( N =22) explored whether and how measured differences in stigma experiences were related to service integration. Results: There were significant differences in perceived status exposure across models of care. After adjustment for potential confounding between sites, those at a partially integrated site and a partially stand‐alone site had greater odds of perceived status exposure than those at the fully stand‐alone site (aOR 3.33, 95% CI 1.98–5.60; and aOR 11.84, 95% CI 6.89–20.36, respectively). There was no difference between the fully stand‐alone and the fully integrated clinic. Qualitative data suggested that many clients at HIV‐only sites felt greater confidentiality knowing that those around them were positive, and support was gained from other HIV care clients. Confidentiality was maintained in various ways, even in stand‐alone sites, through separate waiting areas for HIV testing and HIV treatment, and careful clinic and room labelling. Conclusions: The relationship between model of care and stigma was complex, and the hypothesis that stigma is higher at stand‐alone sites did not hold true in this high prevalence setting. Policy‐makers should ensure that service integration does not increase stigma, in particular within partially integrated models of care.